Director's report of research in Kansas 2009 - Kansas State University. Agricultural Experiment Station (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
This report contains the title, author, and publication information for manuscripts published by station scientists.
DRR09
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects